Caracterização, toxicidade e patogenicidade de Fusarium spp. em genótipos de soja em sistema plantio direto - Milanesi, Paola Mendes (2009)
The sudden death syndrome (SDS), caused by species of Fusarium, is a disease difficult to control and there are no management techniques and resistant cultivars that give long-term positive results. This study aimed to assess populations of Fusarium spp. and Trichoderma spp. associated to eight soybean genotypes, cultivated under no tillage; to determine if the control of Fusarium varies among isolates of Trichoderma; to identify isolates of Fusarium spp. obtained from different genotypes, and to determine their toxicity and pathogenicity to two genotypes of soybean. Soil and roots were collected from experimental plots located at the Fundação Centro de Experimentação e Pesquisa (FUNDACEP), obtaining isolates of Fusarium spp. and Trichoderma spp. There were no differences in the population of Fusarium spp. in plants with symptoms of SDS among the different genotypes. For Trichoderma spp. there was a significant difference among genotypes from plants with and without symptoms of SDS and the genotype CEPS 06006 RR had the biggest population of the antagonist. In the direct confrontation test, eight isolates of Trichoderma spp. obtained the highest score (1) in relation to the control of Fusarium spp. and isolates of Trichoderma spp. from soil of areas with the SDS symptom were more aggressive. Nine species of Fusarium: F. avenaceum, F. solani, F. equiseti, F. Acuminatum, F. kyushuense, F. graminum, F. subglutinans, F. verticillioides and F. lateritium were identified. All isolates promoted internerval chlorosis, necrosis and death of seedlings in the toxicity test. In the pathogenicity test in plants inoculated with the pathogen there was an increase in leaves and roots dry weight and in the number of pods, indicating that there may be species specificity of the species studied in relation to genotype.